2013
DOI: 10.5770/cgj.17.90
|View full text |Cite
|
Sign up to set email alerts
|

Delirium, a Symptom of UTI in the Elderly: Fact or Fable? A Systematic Review*

Abstract: BackgroundIn geriatrics, delirium is widely viewed as a consequence of and, therefore, a reason to initiate workup for urinary tract infection (UTI). There is a possibility that this association is overestimated. To determine the evidence behind this clinical practice, we undertook a systematic review of the literature linking delirium with UTI.MethodsA MEDLINE search was conducted from 1966 through 2012 using the MESH terms “urinary tract infection” and “delirium”, limited to humans, age 65 and older. The sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Broad-spectrum agents were more often used in the elderly population as well. This may reflect treatment-failure or antibiotic resistance, but it could also be caused by the difficulty in determining the site of infection in an elderly deranged patient, causing doctors to prescribe more broad-spectrum to cover a possible respiratory focus as well [26,27]. Also, the ease of administrating quinolones may be contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum agents were more often used in the elderly population as well. This may reflect treatment-failure or antibiotic resistance, but it could also be caused by the difficulty in determining the site of infection in an elderly deranged patient, causing doctors to prescribe more broad-spectrum to cover a possible respiratory focus as well [26,27]. Also, the ease of administrating quinolones may be contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection is related to delirium. A study by Balogun and Philbrick (2014) found that there was relationship between UTI and delirium in the elderly. In subjects with delirium, UTI rates ranged from 25.9% to 32% compared with 13% in those without delirium, and in subjects with UTI, delirium rates ranged from 30% to 35% compared with 7.7% to 8% in those without UTI.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence suggests that antibiotic treatment of bacteriuria improves outcomes in individuals with delirium, falls, confusion, or other geriatric syndromes. 17,18 Guidelines and consensus statements do not recommend testing for, making the diagnosis of, or treating a "UTI" in otherwise asymptomatic, noncatheterized long-term care residents who become delirious, even if they are febrile ( Table 2). Antibiotic treatment for the combination of fever and delirium is accepted, regardless of urinary tract findings, elsewhere in the statement.…”
Section: Delirium and Other Geriatric Syndromesmentioning
confidence: 99%